A single port frequency reconfigurable antenna for underlay/interweave cognitive radio - Laith Wajeeh Abdullah; Adheed H. Saloomi; Ali Khalid Jassim (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
A frequency reconfigurable antenna is presented in this paper as a novel single port system gathering the functionalities of both underlay and interweave cognitive radio. This 25×30×0.8 mm3 system involves a wide slot antenna to cover the ultra wide band (UWB) range with resonating stubs that are used to prohibit/work-only-in specific bands within the UWB frequencies. Here, six positive intrinsic negative (PIN) diodes are used to decide the active sections of the antenna that leads to select its operation as UWB/filtering/multiband antenna. Diodes' configuration results in eight useful operation modes that include a scanning mode, four single band-notch modes and three dual band communication modes. The scanning mode covers the entire UWB range while one of the bands allocated for WiMax, Cband, WLAN or Xband is to be excluded in each of the band-notch modes. On the other hand, each communaication mode is able to work in one of the ranges that cover WiMax/Cband, Cband/WLAN or Xband/international telecommunication union (ITU). S11, realized gain, voltage standing wave ratio (VSWR) outcomes of this design that is simulated by computer simulation technology (CST) v.10 all confirms the proposed system's ability to work in the intended modes. Its novelity to work as interweave/underlay cognitive radio system, highly candidates this design to address many of the UWB communication issues related interference and multiband operation